Developing thin film composite reverse osmosis membrane with high performance by tuning substrate structure - Ong, Jun (Nanyang Technological University, 2021)
Thin-film composite (TFC) membrane is a state-of-the-art membrane mostly deployed in the water treatment and seawater desalination. Despite their good performance at high operating pressure of 50 to 55 bar for seawater reverse osmosis (SWRO) process, the membrane has a relatively low permeability, resulting in high specific energy consumption during desalination process. Therefore, this study was proposed to evaluate the performance of TFC membrane, particularly in the morphology of the porous substrate, long term-stability, permeability and overall salt rejection to distinguish the best substrate that can be used to make TFC membrane with the highest permeability while maintaining high salt rejection, using three different dope solutions to prepare porous polysulfone (PSF) substrate with fully sponge-like, finger-like and the combination of both structures. A thin PA active layer was formed atop each substrate layer via interfacial polymerization (IP). The fabricated membranes were tested under 50 bar in treating synthetic seawater, 35,000 ppm NaCl solution in evaluating the membrane permselectivity. At the same time, the TFC membranes were characterized in term of their substrate pore sizes, cross-sectional morphology and surface topography to investigate the effect of substrate structures on overall membrane performance. At operating pressure of 50 bar, PA-DMF membrane showed the highest permeability of 2.7 L/m2·hr·bar, which was 10 to 15% higher than PA-DMF/NMP and PA-NMP membranes. Regardless the difference in substrate structures, the PA membranes had high rejection towards 35,000 ppm NaCl, achieving rejection of approximate 99%. However, all three membranes exhibited almost similar membrane flux at low operating pressure of 5 bar in treating 2,000 ppm NaCl. Hence, the lower permeabilities of PA-DMF/NMP and PA-NMP membranes were owing to compaction of porous substrate layers that mainly consisted of finger-like structure and macrovoid under high operating pressure, led to greater hydraulic resistance during filtration. Therefore, a substrate that made of sponge-like structure is more preferable in fabricating SWRO membrane as demonstrated by PA-DMF membrane, providing a better support layer for PA layer that more resistant and stable against high operating pressure.